Maximum number of flux lines inside columnar defects - Doria, M. M.; de Andrade, SCB; Sardella, Edson [UNESP] (Elsevier B.V., 2000)
We set new limits for the maximum number of fluxons trapped inside columnar defects, for both cases of metallic and insulated cores. We show that the saturation limit predicted by the Mkrtchyan and Shmidt theory is just a first approximation to our results, because it does not consider the presence of the remaining flux lines exterior to the defects.